(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To Initial establish diagnostic criteria for traditional medicine patterns of benign prostatic hyperplasia (BPH) based on specialized documents. Research Method: Descriptive analysis of clinical conditions and symptoms of Traditional Medicine patterns of BPH based on specialized documents. Selecting conditions and symptoms with a frequency of occurrence > 30% in literature descriptions as diagnostic criteria at the Cronbach’s Alpha confidence level over 60%, thereby constructing diagnostic criteria for traditional medicine patterns of BPH according to symptom groups. Results: Seven patterns of BPH, with a frequency of occurrence of 33% or more described in the literature, with a Cronbach’s Alpha reliability coefficient of 69.1%, accompanied by clinical symptoms with a frequency of occurrence of 33% in specialized literature descriptions at the 62.9% Cronbach’s Alpha confidence level, have been selected as traditional medicine patterns of BPH, including humid heat bladder, heat obstruction in the lungs, obstruction in urethra, stagnation of qi in liver, kidney yin deficiency, kidney yang deficiency, and inadequate middle “qi”. Conclusion: Seven traditional medicine patterns of BPH have been established with a Cronbach’s Alpha reliability coefficient of 69.1%, including symptoms with a probability of occurrence over 30% (Cronbach’s Alpha=62.9%) in Traditional Medicine literature.